Do trade barriers and financial freedom matter in becoming a rich country? - Ang, Joshua; Patalinghug, Jason (Journal of Business and Economic Studies, 2026)
A lot has been written on the impact of economic freedom and its components on economic growth. This paper focuses on financial freedom, which is one aspect of economic freedom. Financial freedom measures how deeply the government is involved in a nation’s financial industry and how that industry is open to foreign competition. The aim of this study is to measure the effect of financial freedom and other factors on gross domestic product (GDP) per capita. We estimate a model using panel data of 184 countries from 2012 to 2019. Our empirical estimations show that financial freedom positively affects per capita GDP, while tariff rates, corporate tax rates, unemployment, and inflation negatively affect per capita GDP.
Keywords: Economic freedom; Financial analysis; Government (linguistics); Gross domestic product; Index of Economic Freedom; Inflation (cosmology); Panel data; Per capita; Tariff; dept.eco

Financial innovation, gender, and credit access: evidence from Ghanaian microenterprises - Thorson, J.A.; Andoh, S. (International Conference on Business Research, 2025)
Keywords: Cash; Closing (real estate); FinTech; Financial inclusion; Financial services; Financial transaction; Mobile banking; Mobile payment; Savings account; dept.eco

Joining farmers’ cooperatives leads to equitable poverty reduction in China – empirical evidence from the rural households survey - Zhang, Ze; Qin, Lijian; Jia, Yu; Li, Yuheng; Hong, Chen; Qin, Wenshuai (Applied Economics, 2025)
Keywords: China; Empirical evidence; Inequality; Poverty; Poverty reduction; Rural poverty; Survey data collection; dept.eco

Will social participation make retirees happier? An empirical study about retirement life in China - Zhao, Luman; Yu, Jia (Journal of Applied Business and Economics, 2025)
How elderlies participate in social activities is a key issue in coping with aging and has an important impact on elderlies’ well-being. This paper examines the effects of different social participation patterns on the happiness of the elderlies in China. The empirical analysis was conducted based on the data from the China Household Finance Survey (CHFS) in 2015. The research results show that compared with reemployment after retirement, community governance is a more common way for retired people to be involved in social activities. We found that reemployment significantly reduces the happiness degree of the retired. Furthermore, this negative effect is more significant in samples without a formal labor contract, relatively lower education level, & senior retired people. In contrast, participating in community governance can significantly improve the happiness level of retirees, which is more essential in the sample of the medium education level and junior retirees.
Keywords: Business; China; Demographic economics; Economics; Empirical research; Labour economics; Life satisfaction; Political science; Psychology; Social psychology; dept.eco

Some determinants of income inequality in Asia and Latin America - Patalinghug, Jason (Valahian Journal of Economic Studies, 2025)
Abstract Income inequality has, in recent years, become a serious issue especially in emerging markets. This paper examines the relationship of income inequality in the Asia-Pacific and Latin America regions to several factors such as gross capital formation, corruption, and per capita gross domestic product (GDP). Using a cross-sectional dataset of 36 countries from both regions for the year 2018 and ordinary least squares regression, the paper shows that gross capital formation and the lack of corruption have a negative and significant relationship with income inequality (as represented by the Gini coefficient). In contrast, per capita GDP has a positive and significant relationship with income inequality. Policymakers who want to rein in income inequality should therefore focus on ways to reduce corruption and increase the formation of capital. This study could be of use for those who are interested in discovering and mitigating the factors that cause income inequality in the developing world.
Keywords: Business; Business informatics; Business management; Demographic economics; Development economics; Economic growth; Economic inequality; Economics; Health care; Income distribution; Inequality; Latin Americans; Mathematics; Political science; dept.eco

Testing for Consistency in Firm Entry and Exit Between the National Establishment Time Series and Business Dynamics Statistics - Kim, Donghyuk; Kim, Younjun; Orazem, Peter; Thomas, Kelsey (Growth and Change, 2026)
Keywords: Business statistics; Census; Consistency (knowledge bases); Dynamics (music); Longitudinal data; Series (stratigraphy); Time series; dept.eco; entrepreneurship; entry; exit; firm data

Bilateral environmental aid under trade competition - Yoon, Sang; Kim, Younjun; Park, Byoung; Yoon, Chang-Ho (Applied Economics Letters, 2026)
Keywords: Bilateral environmental aid; Bilateral trade; Competition (biology); Environmental impact assessment; Environmental policy; Trade barrier; climate finance; dept.eco; energy-saving aid; strategic aid allocation; trade competition

Green banking: prospects and challenges - D'Amora, Emily C.; Andoh, Samuel K (Southwest Business and Economics Journal, 2025)
The paper examines the concept of green banking and sustainable financing, the forces driving green banking, and the reasons for this. The paper suggests that the move toward green banking and financing is the result of environmental degradation and the public’s demand for remediation. As enablers of the industries that create pollution, financial institutions bear a significant responsibility in leading the efforts to curb greenhouse gas emissions. Also, greenhouse gas emissions are the result of market failures; therefore, there is a need for governments to act. The paper also examines the challenges facing green banking and its prospects. The conclusion is that while green banking displays good growth prospects, there exists three major challenges: (1) limited awareness of green products and services that banks can offer, (2) greenwashing, and (3) the high cost of offering green financial services. Despite these challenges, the paper affirms the potential of green banking to promote sustainability and mitigation of the environmental crisis.
Keywords: banking; climate change; dept.eco; environmental crisis; environmental degradation; financial institutions; green banking; greenwashing; peer-reviewed; sustainability; sustainable financing

Unanticipated money growth and unemployment in the Philippines - Patalinghug, Jason C. (Journal of Applied Economic Sciences (JAES), 2024)
The Philippines has had high levels of unemployment for years. During the 2000s, the unemployment rate hovered between seven and ten percent. High unemployment can have adverse effects on individuals and society. The question that this paper analyses is how unanticipated money growth affect the unemployment situation in the Philippines. There has been literature on the relationship between unanticipated growth on the money supply and unemployment. The paper proposes that only unanticipated money movements will affect real economic variables like unemployment and the output level. In order to test our hypothesis, it is important that we need to quantify the concepts of anticipated and unanticipated money movements. This paper uses time-series data on several economic variables as well as a model based on Geetha et al. (2023). Using an error-correction model, the results show that an unanticipated increase in M2 money is a factor that contributes to unemployment in Philippines.
Keywords: Philippines; dept.eco; peer-reviewed; time-series data; unanticipated money; unemployment

What increases the urban–rural gap in firm entry rates? - Kim, Younjun; Orazem, Peter (Small Business Economics, 2025)
Keywords: Agglomeration; Business; Economic geography; Economics; Entrepreneurship; Finance; Firm entry; Human capital; J24; M13; R11; Rural; Urban; dept.eco; peer-reviewed

Corruption, Natural Capital and Economic Development: A Dynamic GMM Analysis - Ang, Joshua; Patalinghug, Jason (Review of Economic Analysis, 2025)
Using a dynamic panel dataset of 150 countries for the period of 2006-2018 and a two-step system GMM estimation model, this paper shows that natural resources have a positive effect on economic development while holding corruption constant. Our findings support the notion that natural resources have a positive effect on the economy of a nation. When a country has less corruption, it improves the appropriation of economic gains from natural resources which serves as natural capital that would drive further capital accumulation and further development. We also find that physical capital, human capital, and freedom from corruption show strong positive effects on economic development, controlling for other economic and institutional variables.
Keywords: Corruption; Dynamic Panel Study; Econometrics; Economic Development; Economics; Human Capital; Language change; Natural Resources; Physical Capital; dept.eco

Information technology adoption and the growth of nonemployer businesses - Kim, Y.; Thompson, E. (Journal of Economics and Management Strategy, 2024)
The growth of nonemployer businesses as a share of the working-age population has been little studied relative to the decline of employer business rate in the United States. We show that local labor markets specializing in routine task-intensive jobs have experienced a higher adoption of information technology as well as the growth of nonemployer businesses primarily through increasing self-employment in nonroutine manual task-intensive jobs that are less frequently outsourced to business service firms. © 2024 Wiley Periodicals LLC.
Keywords: dept.eco; peer-reviewed

How human capital prevents intergenerational poverty transmission in rural China: Evidence based on the Chinese general social survey - Chen, Hong; Yu, Jia; Zhang, Ze; Li, Yuheng; Qin, Lijian; Qin, Mingshuai (Journal of Rural Studies, 2024)
Keywords: dept.eco; peer-reviewed

Challenges and Futures of Long-Term Care Industry after COVID-19 Pandemic - Yu, Jia (Psychosocial, Educational, and Economic Impacts of COVID-19, 2022)
COVID-19 pandemic has affected people’s daily life dramatically since December 2019. More than 211 million cases and 4.42 million deaths have been reported and confirmed all over the world. Long-term care facilities are taking the biggest hit during this pandemic, even after the spread-out of the vaccines. Globally, residents in long-term care facilities have experienced disproportionately high morbidity and mortality from COVID-19. Elderlies residing in long-term care facilities have the greatest susceptibility to COVID-19 and the poorest outcomes from infections. This chapter overviewed the insight, impact, and challenges of COVID-19 on the residential care homes in UK, US, and Australia and provided possible implications for the long-term care market post-pandemic.
Keywords: dept.eco

The Effect of Property Rights on GDP per Capita - Ang, Joshua Ping; Patalinghug, Jason C. (The Empirical Economics Letters, 2020)
Keywords: dept.eco; peer-reviewed

COVID-19: effectiveness of socioeconomic factors in containing the spread and mortality - Book Chapter - Patalinghug, Joshua Ping Ang, Fang Dong, Jason (The Political Economy of Covid-19, 2022)
This paper presents a study on 80 countries that evaluates the socioeconomic factors in containing the spread and mortality of COVID-19. Our results show that the long-term social factors such as lower personal freedom, better education in science, and past coronavirus outbreak experience are more effective than the economic factors such as higher healthcare-associated factors per 1000 population and larger GDP. However, using GDP per capita as the instrumental variable, we also find that the richer countries with a high degree of personal freedom have a higher number of infection or death cases per million population because they would be less likely to adhere to and implement the policy of the movement restrictions to restrict their access to goods and services.
Keywords: dept.eco

Bilateral environmental aid and trade - Yoon, Sang W.; Kim, Younjun; Park, Byoung G.; Yoon, Chang-Ho (Applied Economics, 2024)
The paper estimates the determinants of the growing volume of bilateral environmental aid for the mitigation of climate change using an empirically testable multilateral framework in which both donors and recipient countries compete in world export markets. As the potential donors weigh environmental benefits against the economic costs of providing aid, strategic interactions between the donors and the recipient countries as well as among the donors, influence the evolution of environmental aid. The paper shows that while the volume of bilateral environmental aid increases with the recipient country’s credible environmental commitment and bilateral trade volume, the competitive pressure in the export market reduces bilateral environmental aid. Free-riding incentives prevail among the individual donors, whereas the multilateral environmental aids that aim to restore the loss of global environmental resources without altering individual trade competitiveness can increase bilateral environmental aids.
Keywords: Environmental ODA; F18; F35; Q54; competitive threats; credible commitment; dept.eco; international trade; multilateral institutions; peer-reviewed

Sustainable growth with pollution augmenting technological changes - Yoon, Sang Won; Yoon, Chang-Ho (2023)
Disruptive technological changes, including carbon capture and storage, can have macroeconomic rebound effects that pose a threat to long term environmental sustainability when not accompanied by pollution taxes. The paper demonstrates that when the elasticity of intertemporal substitution is less than one, implementing a Pigouvian tax effectively stabilizes pollution emissions, regardless of technical and consumption elasticities of substitution. However, if the elasticity of intertemporal substitution exceeds one, flexibility in technical or consumption substitution could cause sustainable growth to falter. The policy implications concerning the role of subsidies for clean technology are discussed.
Keywords: Elasticity of intertemporal substitution; Optimal pollution tax; Sustainable development; dept.eco; energy rebound; technological change

International comparison on economics impact from the COVID-19 pandemic: policy analysis - Supple, Brandon; Yu, Jia (Medical Research Archives, 2023)
Keywords: SCSU-student; dept.eco; peer-reviewed

The Philippines in a Liberalizing Trade Environment: Issues and Prospects - Patalinghug, Jason (Economic Insights - Trends & Challenges, 2020)
Free trade agreements (FTAs) have mushroomed in the Asia-Pacific region over the past fifteen years. The Philippines is trying to forge several of these agreements in order to stay competitive. This paper examines the emergence of the Association of South East Asian Nations (ASEAN) as well as the ASEAN Free Trade Agreement. This paper will discuss the advantages for the country by joining both the AFTA and the Japan Philippines Economic Partnership Agreement. It will also discuss several free trade agreements that are in effect in the region as well as efforts by the country to join the Trans-Pacific Partnership (TPP) and the Regional Comprehensive Economic Partnership (RCEP). For the country to be a member of the TPP certain institutional reforms are needed to be put in place. The studies examined in this paper show that these FTAs in general have a positive effect on the Philippine economy.
Keywords: PHILIPPINES; REGIONAL Comprehensive Economic PartnershipCOMMERCIAL treatiesTRANS-Pacific PartnershipFREE tradePARTNERSHIP agreements; dept.eco; peer-reviewed; ⛔ No DOI found

Unlocking Opportunities for Migrant Workers in China: Analyzing the Impact of Health Insurance on Hukou Switching Intentions - Chen, Hong; Yu, Jia; Qin, Mingshuai; Wang, Yangyang; Qin, Lijian (Sustainability, 2023)
The Chinese urban–rural binary health insurance structure has contributed to a significant urban–rural segmentation and regional fragmentation, which will affect labor mobilization and urbanization. The purpose of this research is to study whether and how urban–rural binary health insurance impacts the intentions of migrant workers to switch between rural and urban hukou. Pooled data were drawn from China Migrants Dynamic Survey, collected by the National Health Commission of China. The study applied the instrument variable model due to the existence of the endogeneity; and the IVprobit model to conduct the empirical analysis. Our findings are as follows: (1) the urban–rural binary health insurance affects migrant workers’ intentions to switch to urban hukou significantly. (2) The negative impact of originally rural health insurance on migrant workers’ intention of switching to urban hukou is relatively large for low-education-level migrant workers. (3) Compared with new generation of migrant workers, old migrant workers have higher health insurance dependency levels. Finally, our research suggested several policy implications, such as accelerating the establishment of a unified urban–rural health insurance system, increasing the urban health insurance participation rate of migrant workers in their working cities, and including migrant workers in the scope of equal access to urban public services, etc. All the policy suggestions are essential in order to accelerate the citizenization of migrant workers, improve the quality of urbanization, and promote the construction of a unified national labor market.
Keywords: dept.eco; intention of switching to urban hukou; migrant workers; peer-reviewed; urban–rural binary health insurance

Overconfidence and Public Intoxication Arrest: Evidence from a University Town Police Log - Hoffman, Elizabeth; Kim, Younjun (The B.E. Journal of Economic Analysis & Policy, 2022)
We show that overconfident individuals are likely to be arrested for public intoxication by using arrest records from a university town police log. This relationship is robust to various control variables such as risk aversion, time discounting, present bias, self-control, selfishness, loss aversion, and socializing with peers arrested for public intoxication. However, this relationship is no longer significant using only self-reported arrest data. We hypothesize that overconfident individuals are likely to underreport their arrests. This result has important implications for the use of self-reported data on public intoxication arrests rather than actual arrest records.
Keywords: arrest; dept.eco; overconfidence; public intoxication

'How could I choose my health insurance plan?' Determinants of employer-sponsored health insurance plan selection: application of machine learning technique - Zhang, Yi; Yu, Jia (International Journal of Economics and Business Research, 2022)
Selecting the appropriate, reasonable, and affordable health insurance plan becomes a very important question to solve for both employers and employees. Our research tries to locate the factors determining private sector health insurance plan enrolment decision, and also provides a guideline to both private companies and employees on health insurance plan selection strategies. By using Kaiser Family Foundation Annual Employer Health Benefits Survey (KFF EHBS) data, we apply random decision forest machine learning methodology to study the determinants of employees' health insurance selection, as well as to compare the prediction accuracy among different methodologies. The results indicate: 1) the employees at large firms and the firms with higher eligible rate would tend to choose PPO plan; 2) employees who need family coverage would have different choices comparing employees who seek for single coverage only; 3) employer's contribution and annual total contribution to the health insurance plan are the most important determinants on employees' insurance selection. The conclusion also can provide some suggestions to insurance companies on health insurance package design for different types of employers and employees.
Keywords: HDP; PPO; dept.eco; health insurance; high-deductible health plan; logit regression; machine learning; peer-reviewed; random decision forest

Routine-biased technological change and declining employment rate of immigrants - Kim, Younjun; Thompson, Eric (Eastern Economic Journal, 2021)
We find that routine-biased technological change decreases the employment-to-population ratio of foreign-born population over the last three decades (1980–2010). This impact is greater for foreign-born population with lower English proficiency. As computerization and automation substitute for workers in routine occupations, switching from routine jobs to non-routine cognitive jobs may be more challenging for foreign-born workers than for native workers. © 2021, EEA.
Keywords: dept.eco

Property rights and economic growth: A dynamic GMM analysis - Ang, J.; Patalinghug, Jason (Economics Bulletin, 2021)
This paper examines the role of property rights and other factors to the growth of real gross domestic product (GDP) per capita. We show using a two-step system generalized method of moments (GMM) dynamic model and a panel data set of around 150 countries from 2006 to 2018 that property rights have a positive and significant effect on the growth of real GDP per capita. The paper also found that human capital, physical capital and inflation have significant effects on real GDP per capita growth. © 2021. All Rights Reserved.
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found

Property, Institutions, and Social Stratification in Africa - Andoh, Samuel K. (African and Asian Studies, 2020)
Keywords: book.review; dept.eco

Which Small Towns Attract Start-Ups and Why? Twenty Years of Evidence from Iowa - Artz, Georgeanne M.; Kim, Younjun; Orazem, Peter F.; Han, Peter J. (American Journal of Agricultural Economics, 2021)
Using data on a sample of small Iowa towns consistently collected over two decades, we investigate how agglomeration economies, social capital, human capital, local fiscal policy, and natural amenities affect new firm entry. We find that human capital and agglomeration are more conducive to new firm entry than are natural amenities, local fiscal policy, or social capital. The impact of local fiscal policy is too small to overcome the locational disadvantages from insufficient endowment of human capital and agglomeration. A rural development approach that encourages firm entry in rural towns with the largest endowments of human capital and market agglomeration would be more successful than trying to raise firm entry in every town.
Keywords: M13; R11; R39; agglomeration; dept.eco; firm location; human capital; peer-reviewed; rural

Economic development in Ghana and Malaysia: A comparative analysis - Andoh, S.K.; de Gannes Scott, B.J.; Ofori-Abebrese, G. (Economic Development in Ghana and Malaysia: A Comparative Analysis, 2020)
Economic Development in Ghana and Malaysia investigates why two countries that appeared to be at more or less the same stage of economic development at one point in time have diverged so substantially. At the time of their independence from the UK in 1957, both Ghana and Malaysia were at roughly the same stage of economic development; in fact, Ghana's real per capita income was slightly ahead of Malaysia's. Since then, Ghana's development has been sluggish, while Malaysia's economy has taken off into sustained growth and today, the real per capita income of Malaysia is about five times that of Ghana. This volume examines the pre-colonial and colonial economies of both countries, and the economic policies pursued after independence. In doing so, it aims to identify policies which might have contributed to Malaysia's development and those which might have slowed Ghana's. The authors ask whether lessons can be learned from the successes of countries such as Malaysia. This detailed comparative analysis will be useful to students and researchers of development economics as well as public policy makers in developing countries. It is written in language which makes it accessible to the general reader. © 2020 Samuel K. Andoh, Bernice J. deGannes Scott and Grace Ofori-Abebrese. All rights reserved.
Keywords: dept.eco; peer-reviewed

COVID-19: effectiveness of socioeconomic factors in containing the spread and mortality - Ang, Joshua Ping; Dong, Fang; Patalinghug, Jason (International Review of Applied Economics, 2021)
This paper presents a study on 80 countries that evaluates the socioeconomic factors in containing the spread and mortality of COVID-19. Our results show that the long-term social factors such as lower personal freedom, better education in science, and past coronavirus outbreak experience are more effective than the economic factors such as higher healthcare-associated factors per 1000 population and larger GDP. However, using GDP per capita as the instrumental variable, we also find that the richer countries with a high degree of personal freedom have a higher number of infection or death cases per million population because they would be less likely to adhere to and implement the policy of the movement restrictions to restrict their access to goods and services. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: COVID-19; Coronavirus; Gross Domestic Product; dept.eco; disease control; disease spread; epidemic; global perspective; mortality; pandemic; peer-reviewed; regression analysis; socioeconomic conditions

Derivative use, ownership structure and lending activities of US banks - Abugri, Benjamin A; Osah, Theophilus Teye (Journal of Economics and Finance, 2021)
Following the 2007–2008 financial crisis, there is widespread interest in understanding how derivative use drives bank lending behavior. Our paper examines the impact of bank ownership structure on the relationship between derivative use and lending activities of U.S. banks. We find that lending recovered faster in larger banks than smaller banks post-crisis and in line with Diamond’s (Diamond DW 1984 Financial intermediation and delegated monitoring. Rev Econ Stud 51:393–414) systemic risk reduction theory, derivative use is positively associated with lending growth. Ownership is significant in explaining the magnitude of the relationship even after controlling for alternative specifications of the derivative use variable. In both normal and crisis periods, the speed of adjustment of lending to derivatives use by stock banks lags that of mutual banks. We suggest that speculative trading in derivatives substitutes for lending growth to a larger extent for stock banks compared to mutual banks. These findings may have important implications for investors and bank regulators. © 2020, Academy of Economics and Finance.
Keywords: dept.eco; dept.fin; peer-reviewed

No more nursing homes? Changes in consumer preferences for long-term care facilities following COVID-19 - Schultz, Amber F; Yu, Jia (British Journal of Healthcare Management, 2020)
Since the first COVID-19 case was discovered in December 2019, over 12.1 million cases have been reported in more than 188 countries and territories. In the USA, the Centers for Disease Control and Prevention has confirmed almost 3.05 million COVID-19 cases, with more than 132 000 deaths. The COVID-19 pandemic has had a particularly dramatic impact on the elderly and those with chronic underlying medical disorders. Before the second outbreak in July, long-term care facilities were the most severely affected in terms of case numbers, especially nursing homes. This article provides information and insight into the potential changes in consumer preferences toward long-term care facility selection and the possible structural change of the long-term care industry in three aspects; structure, conduct and performance. © 2020 MA Healthcare Ltd. All rights reserved.
Keywords: Covid-19; Home care service; Long-term care facility; Nursing home; dept.eco; peer-reviewed

Cost containment of total knee arthroplasty in the us: DWA analysis on regional cost and clinical comparison between 2010 and 2013 - Ball, Alexandra M.; Yu, Jia (Health, 2020)
Keywords: dept.eco; peer-reviewed

Genetically modified crops’ environmental impact and trust in eco-labels - Kwak, Lynn E.; Yoon, Sang Won; Kim, Younjun (Australasian Marketing Journal, 2020)
The U.S. Department of Agriculture expects companies to disclose genetically modified (GM) ingredients in foods and beverages by January 2022. While food companies fear that the stigma of GM labels could cause GM food sales to decline, eco-labeling could lessen the impact of GM-labeling. The results of the present research indicate that neither the eco-labeling alone nor the eco-labeling accompanied by information about the environmental benefits of GM crops influence consumers’ willingness to buy. Based on the mediation analysis, however, trust of eco-labels mediates the relationship between GM foods’ environmental friendliness information and consumers’ willingness to buy eco-labeled GM food. The theoretical and practical implications of the findings are discussed. © 2020
Keywords: Eco-labeling; Genetically modified (GM) foods; Trust; Willingness to buy; dept.eco; dept.mkt; peer-reviewed

‘Is it wise to open up America again now?’ Learning from government responses to COVID-19 and economy reopen points in three Asia-Pacific countries - Yu, Jia; Pang, Yulei (British Journal of Healthcare Management, 2020)
With the continuously increasing number of new confirmed COVID-19 cases, many health experts worried about the possibility of a ‘second wave’ outbreak, which might cause more deaths and hit economies even worse. This article looks at the experiences of fighting COVID-19 from three Asia-Pacific countries and discusses whether it is a wise decision to open up America again at this time.
Keywords: dept.eco; dept.mat; peer-reviewed

Sustainable development: Structural transformation and the consumer demand - López, Ramón E.; Yoon, Sang W. (Structural Change and Economic Dynamics, 2020)
This paper examines the feasibility of environmentally sustainable growth in a competitive market economy assuming various types of technological changes affecting pollution emissions and ultimately climate change. We consider two final outputs and two factors of production, accounting for both pollution flow and stock effects. If the initial level of pollution emissions satisfies certain boundary conditions, a Pigouvian pollution tax may assure sustainable growth without any further government intervention. This is true even if exogenous technological change is assumed to benefit exclusively the pollution-intensive industries (the “dirty” sector). A consumers’ composition effect (often neglected in the literature), driven by an endogenous change in the relative prices between clean and dirty final goods under an optimal pollution tax, plays a critical role in the structural transformation process to achieve long-run sustainable economic growth.
Keywords: Consumption flexibility; Optimal pollution tax; Sustainable development; Technological change; boundary condition; dept.eco; economic growth; emission; environmental economics; pollution tax; sustainable development; technological change

ICT and transport infrastructure development: an empirical analysis of complementarity - Na, Kyoung Y.; Kim, Dong H.; Park, Byoung G.; Yoon, Sang W.; Yoon, Chang-Ho (Applied Economics, 2020)
This paper provides an empirical framework to assess the nonlinear complementary linkage effects that arise from the interaction between motorway capital and information and communications technology (ICT) capital in developed economies. Using panel data from the Organisation for Economic Co-operation and Development (OECD) member countries and controlling for endogeneity, the paper finds that there exists a critical mass for ICT capital such that if the capital grows beyond the critical mass, the marginal contribution of motorway capital to productivity growth increases as the motorway is extended. This empirical result explains variations in the productivity contributions of transport infrastructure across countries that differ in their ICT infrastructure and has implications for setting the investment priorities of key components of infrastructure. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: ICT capital; OECD; complementarity; dept.eco; empirical analysis; information and communication technology; infrastructural development; infrastructure development; motorway; panel data; peer-reviewed; productivity; productivity growth; transportation infrastructure

The intra-industry effects of proxy contests - Chen, Fang; Huang, Jian; Yu, Han (Journal of Economics and Finance, 2020)
In this study, we examine the intra-industry effect of proxy contests. Proxy contests convey the information of common industrial risks or expected competitive relationship change. We find significant negative abnormal returns in the group of competitors of target firms with negative abnormal returns, and such negative abnormal returns become larger for similar-size competitors. In contrast, there are no significant abnormal returns for competitors of target firms with positive abnormal returns. These findings are consistent with the information-based theory but not the competitive theory. © 2019, Academy of Economics and Finance.
Keywords: Competitive effect; Information-based effect; Intra-industry effect; Proxy contest; dept.eco; dept.fin; peer-reviewed